OP032 Outcome of pregnancies in female IBD patients treated with vedolizumab. (16th January 2018) - Moens, A; van Hoeve, K; Humblet, E; Rahier, J -F; Bossuyt, P; Dewit, S; Franchimont, D; Macken, E; Nijs, J; Posen, A; Van Hootegem, A; Van Moerkercke, W; et al.
Abstract: Background: Vedolizumab (VDZ) is a gut-targeted IgG1 anti-α4β7 integrin approved for treatment of inflammatory bowel disease (IBD). As IBD typically affects women at childbearing age, studies on pregnancy outcomes in patients under VDZ are important. Animal studies showed that MAdCAM-1, the ligand for α4β7-integrin, is expressed by maternal vessels during placental development and α4β7-expressing cells of the macrophage/monocyte lineage are therefore considered important in maternal/foetal tolerance. Blocking this interaction by VDZ might affect this process. Methods: This retrospective, national observational study evaluated the outcome of pregnancies in IBD patients under VDZ. Details on disease activity, prenatal complications, delivery and neonatal outcome were collected. Results: A total of 23 pregnancies were reported. All but five women had disease remission at conception. There were 18 live births (72% female, incl. two twins), two interrupted pregnancies and five pregnancies are still ongoing. Maternal characteristics are displayed in Table 1. Patients, who remained in remission ( n = 12), reported the following complications: intra-uterine growth retardation ( n = 1), eclampsia ( n = 1), premature rupture of the membranes ( n = 2) and congenital malformation ( n = 2, hip dysplasia and pulmonary valve stenosis). Of the five patients with active disease at conception, three pregnancies were unaffected, one female lost her foetus due to chorioamnionitis at week 22 and one had an active termination due to relational problems. One patient flared during pregnancy and delivered a child with Hirschsprung's disease. VDZ was continued throughout pregnancy in two females and was stopped in the first, second and third trimester in 4, 11, and 1 patient, respectively. The median (IQR) gestational age, Apgar score at birth and birth weight were respectively 39 (37–39.4) weeks, 9 (9–9) and 3305 (2823–3698) grams. Eight children were breastfed for a median (IQR) of 10 (4–26) weeks. All newborns were vaccinated according to the standard Belgian regimen with 44% receiving Rotavirus vaccination. No serious infections or malignancies were reported during the first year of life. Conclusions: This is the largest cohort study on pregnancy outcomes in patients treated with VDZ. Despite the still low number of pregnancies, we observed a number of prenatal complications and congenital malformations, which urges more studies on the function of α4β7-MAdCAM1 interaction in the placenta. In the meanwhile, vigilance and strict follow-up of pregnant IBD patients treated with VDZ is necessary.